The pore-scale mechanisms of surfactant-assisted spontaneous and forced imbibition in water-wet tight oil reservoirs - Cao, Bao (2022)
The imbibition of water with surfactants, including spontaneous imbibition and forced imbibition, is of great significance for enhanced oil recovery (EOR) in tight sandstone reservoirs. Up to now, the migration behaviors of the water and the oil in pores of different sizes, as well as the mechanisms of both spontaneous imbibition and forced imbibition with different surfactants, have not been comprehensively addressed yet. This work first measured the oil-water interfacial tensions (IFTs) and the contact angles in oil-water-rock system with two types of surfactants, namely medium-IFT (0.1–10 mN/m) and low-IFT (0.001–0.1 mN/m) surfactants, at different concentrations to comprehend the functionalities of surfactants on oil recovery. Secondly, the pore size distributions of tight sandstones were determined by the high-pressure mercury intrusion (HPMI) and the nuclear magnetic resonance (NMR) technology to characterized the pores into three types (micropores, mesopores, and macropores) according to the pore sizes. Eventually, this work presented the oil recovery results in these three types of pores for spontaneous and forced imbibition using the two types of surfactants in water-wet tight core samples. Both spontaneous and forced imbibition results showed that the oil recoveries with surfactants were higher than those with brine, which was primarily attributed to the increased oil in the mesopores and the macropores. However, the addition of low-IFT surfactants apparently reduced the oil recovery in micropores, hence resulted in a lower oil recovery in comparison with the medium-IFT surfactants. It was also found that the oil in micropores contributed more than 50% of the oil recovery in the imbibition, except for the imbibition with low IFT, due to the high initial oil volume ratios in micropores; there could be a moderate IFT value (e.g., 0.1–1 mN/m) with the use of surfactants to obtain the highest oil recovery. Moreover, in comparison with the spontaneous imbibition, the forced imbibition could enhance the imbibition of water into the micropores but prevent the oil from being extracted from the mesopores and the macropores, which consequently led to a higher contribution of the micropores on oil recovery than that of the larger pores, especially the mesopores.